Analysis of autonomic modulation after an acute session of resistance exercise at different intensities in chronic obstructive pulmonary disease patients - Nicolino, Juliana [UNESP] (2015)
Purpose: Physical exercises are employed as part of the treatment of patients with chronic obstructive pulmonary disease (COPD); however information regarding cardiac autonomic modulation after an acute session of resistance exercise (RE) is unknown. The aim of this study was to evaluate the cardiac autonomic modulation, via heart rate variability after an acute session of RE applied at different intensities in COPD patients.Patients and methods: Twelve COPD patients underwent an acute session of RE with an intensity of 600% and another of 9000 of the one repetition maximum test. For analysis of autonomic modulation, heart rate was recorded beat-by-beat for 20 minutes at rest and after the training session. Heart rate variability indexes were obtained in the time and frequency domains for the assessment of autonomic modulation.Results: Regardless of exercise intensity, RE acute sessions influenced the autonomic modulation the recovery period was compared with the baseline. An increase in standard deviation of normal to normal RR intervals was observed throughout recovery time after the RE, as compared to baseline in both protocols: 60% and 90% of the one repetition maximum test. The spectral component of low frequency index (ms) was higher throughout recovery when compared to baseline in both protocols. The same was also observed in the spectral component of high frequency index (ms) for the protocols of 60% and 90%.Conclusion: RE sessions impact on the autonomic modulation of COPD patients by promoting differences in the recovery period compared to baseline, regardless of the intensity of the exercise performed.